The Moderation Role of Dividend Per Share on the Relationship between Earning Per Share and Return on Equity on Stock Prices - Muh Nur; Ummy Kalsum; Mahmudin A Sabilalo; Laode Sahili; Rince Tambunan (International Journal of Artificial Intelligence Research, 2022)
This study examines and proves whether there is an effect of Dividend Per Share (DPS) in moderating the relationship between Earning Per Share (EPS) and Return on Equity (ROE) on stock prices in food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2019-2021. This type of research is associative research. The sampling technique used is purposive sampling. The data used is secondary data in the form of financial statements. This data will be analyzed using multiple linear regression analysis method, namely descriptive statistical method used to analyze data for more than two research variables. To test the regression with moderating variables using the Moderating Regression Analysis (MRA) Test. Hypothesis testing used is t-test, F-test, and coefficient of determination (R2). This study produced four findings as stated in the research hypothesis. First, Earning Per Share (EPS) has a significant effect on stock prices. Second, Return on Equity (ROE) has no significant effect on stock prices. Third, the interaction variable Earning Per Share (EPS) with Dividend Per Share (DPS) is a moderating variable, so that DPS can strengthen the relationship between Earning Per Share (EPS) on stock prices. Fourth, the interaction variable Return On Equity (ROE) with Dividend Per Share (DPS) cannot strengthen the relationship of Return On Equity (ROE) to stock prices.